Corporate Social Responsibility and Firm Financial Performance: Moderating role of Ethical Leadership and Social Capital - Sadia Butt; Iqra Mubeen; Adeel Ahmed (JISR Management and Social Sciences & Economics, 2022)
This study examines the relationship between corporate social responsibility (CSR) and the firm financial performance in Pakistan with the mediating role of ethical leadership and social capital between CSR and financial performance. Data was collected by applying random probability sampling from 178 respondents through a survey method from employees of non-financial PSX listed firms. Linear regression was conducted through SPSS to test hypotheses. The regression results confirmed a positive and significant relationship between CSR and financial performance. The results further reveal a positive significant moderating role of ethical leadership between CSR and financial performance but no moderating role of social capital between CSR and financial performance. The study has implications for both scholars and management. The study has implications for both scholars and practitioners. The results reveal the vital role of a leader ethical conduct in implementing CSR practices and its positive effect on financial performance of an organization.